2020
DOI: 10.5114/aoms.2019.88019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cognitive-behavioral therapy on depression in dialysis patients – meta-analysis

Abstract: Introduction: Depressive disorders are the most common mental health problem among patients undergoing dialysis. Furthermore, depression is an independent factor increasing the mortality and frequency of hospitalization in this group of patients, yet psychological intervention programs aimed at improving the mental health of dialysis patients have still not been developed. This meta-analysis aimed to assess the effects of cognitive-behavioral therapy on depressive symptoms in dialysis patients. The main hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Studies in patients with CKD have found an increased risk of mood disturbances and emotional problems, such as depression and anxiety (Drew et al., 2019; Schouten et al., 2020; Tanaka & Okusa, 2020; Tian et al., 2019; Viana et al., 2019), which in turn can also be related to cognitive impairment in affected patients (Bronas et al., 2017; Drew & Weiner, 2014; Viana et al., 2019). In fact, despite the high incidence of these cognitive and emotional disorders reported in earlier studies, these conditions are most likely underdiagnosed in patients with CKD (Gerogianni et al., 2019; Zegarow et al., 2020). Thus, the positive perception of cognitive health and emotional well‐being reported by patients and carers in this study is not in line with the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in patients with CKD have found an increased risk of mood disturbances and emotional problems, such as depression and anxiety (Drew et al., 2019; Schouten et al., 2020; Tanaka & Okusa, 2020; Tian et al., 2019; Viana et al., 2019), which in turn can also be related to cognitive impairment in affected patients (Bronas et al., 2017; Drew & Weiner, 2014; Viana et al., 2019). In fact, despite the high incidence of these cognitive and emotional disorders reported in earlier studies, these conditions are most likely underdiagnosed in patients with CKD (Gerogianni et al., 2019; Zegarow et al., 2020). Thus, the positive perception of cognitive health and emotional well‐being reported by patients and carers in this study is not in line with the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Recently published results from the European QUALity (EQUAL) study, an ongoing, prospective, multicenter study in patients ≥65 years with an incident eGFR ≤20 mL/min/1.73 m 2 highlighted the number of symptoms and severity of symptom burden considerably worsened before dialysis initiation among advanced CKD patients, of which some improvements in cardiopulmonary symptoms, gastrointestinal symptoms, neurological symptoms, emotional symptoms, sleep disorders, and fatigue were observed while sexual symptoms (e.g., "decreased interest in sex" and "difficulties in becoming sexually aroused"), integumentary, and musculoskeletal symptoms worsened following dialysis initiation or did not change at all [73]. Table 3 outlines some of the common symptoms that may be experienced by older PD patients and potential management strategies to address these symptoms [15,[74][75][76][77][78][79][80][81].…”
Section: Addressing Symptom Burden In Older Pd Patientsmentioning
confidence: 99%
“…Key biochemical parameters to monitor for include hypokalemia and hypoalbuminemia. The P-DOPPS showed that hypokalemia may reflect underlying PEW in PD patients and predict peritonitis and Fatigue and lack of energy [15] • Investigating and treating the factors leading to fatigue and lack of energy, e.g., sleep hygiene, stress, depression, malnutrition as fatigue, and lack of energy most likely a secondary symptoms from a root cause Depression [15,74,75] • CBT sessions • Counseling with patient and families/caregivers to ensure adequate support while on PD is provided • Encourage regular physical activity • Anti-depressant medications may be required in more severe cases Poor sleep [15,76] • Counseling and advise to generate a sleep schedule • Create a restful environment and remove stressors which may affect sleep • To manage sleep apnea if present • In prolonged insomnia, sleeping pill prescription may be needed Pain [77] • Aim for early identification of pain symptoms by families and caregivers as elderly patients may not always be able to communicate their pain symptoms due to cognitive impairment • Review of the catheter position and PD infusion regime as drain and infusion pain are common • Over-the-counter as needed/regular pain relief and opioids may be required Restless legs [78] • Dopaminergic therapy (i.e., levodopa or dopamine receptor agonists such as pramipexole) is usually first line • Gabapentin, benzodiazepines, and opioids are suitable alternatives Pruritus [79] • Current pharmacological options include antihistamines, opioids, and gabapentinoids • Non-pharmacological options include phototherapy, acupuncture/acupressure, and fatty acid supplementation Poor appetite [80] • Use of icodextrin-based PD solutions may improve appetite due to reduced appetite inhibition • Appetite stimulants (e.g., megesterol acetate, cannabinoids, and cyproheptadine) can improve appetite, caloric intake, and nutritional and inflammatory status in patients receiving PD Constipation [81] • Rule out secondary causes (e.g., bowel obstruction)…”
Section: Addressing Symptom Burden In Older Pd Patientsmentioning
confidence: 99%
“…Several conclusions can be drawn from clinical trials in recent years: first, the types of nonpharmacological therapy are diverse, including psychological education, cognitive-behavioural therapy (CBT), relaxation training and physical therapy and the related methods such as individual psychological intervention; telephone care; exercise programmes; self-management; and group, music, problem-solving, meditation and laughter therapies. Second, CBT is shown to improve symptoms of depression in patients on maintenance dialysis [91,92 ▪▪ ]. Third, except for the study by Griva et al [93], most follow-up periods comprised only a few weeks; therefore, comprehensive studies of long-term effects of nonpharmacological therapies are warranted.…”
Section: Treatmentmentioning
confidence: 99%
“…Third, except for the study by Griva et al [93], most follow-up periods comprised only a few weeks; therefore, comprehensive studies of long-term effects of nonpharmacological therapies are warranted. Studies have shown that nonpharmacological therapy has significant clinical effects for treating dialysis patients with depression (see Table 3) [92 ▪▪ ,93–101].…”
Section: Treatmentmentioning
confidence: 99%